Exposición A La Violencia Y Su Relación Con La Salud Mental En Estudiantes De Educación Media Superior En Ciudad Juárez, México - Chávez, Carlos Eduardo Farfán; Del Villar, Oscar Armando Esparza; Alvarado, Priscila Montañez; Ramírez, Luz Adriana Orozco (European Scientific Journal, ESJ, 2017)
Ciudad Juarez, Mexico, received the classification of the most dangerous city in the world for their high rates of violence during the years 2007-2012; five years of intense stress, deterioration in confidence to the authorities and fears. Citizens during this period were acquaintances, friends, relatives, neighbors, someone violated, and in the worst cases victims of organized crime. Many people in Ciudad Juarez were victims or witnesses of communal violence. With violence experienced in Ciudad Juarez from 2007, we want to analyze the relationship between exposure of violence with symptoms of depression, post-traumatic stress and thoughts paranoid in young people attending high school. The objective was to analyze the relationship between the level of exposure to violence with symptoms of depression, posttraumatic stress and thoughts paranoid in students of middle school in Juárez, Mexico City. Analyzed the relationships between exposure to violence with depression, post-traumatic stress and thoughts through Pearson correlations paranoid obtaining statistically significant correlations, so that greater exposure to violence were reported higher levels of depression, posttraumatic stress disorder and paranoid thoughts. It can be concluded, looking at the results, positive correlations indicate that greater exposure to community violence, greater is the presence of depressive symptoms, posttraumatic stress disorder and paranoid thoughts.